Croatian Railways as a Subject in the European Transport Market - Bogović, Blaž; Mlinarić, Tomislav (Promet - Traffic&Transportation, 2012)
The paper considers the environment and the tasks that theCroatian railways need to carry out in order to gain importancewithin the European transport market. It deals with the economicvalues that may be expected from the modernised railways.Therefore, the Croatian railways will have to undergotechnical, technological and organisational restructuring. Themarketing concept of meeting the customers’ needs and demandshas to be developed. The marketing is meant and,among other things, the selection and definition of those segmentsin which the Croatian railways could do business successfully.These include: passenger traffic - suburban, then interurban(domestic and international in and out) and, accordingto the needs of the European railways, transit traffic. Ingoods transport - to identify the needs of big users and define thesize of the offer accordingly.Although the paper could not deal with concrete restructuringtasks (which is the first and foremost task of the CroatianRailways), it indicates the main directions. These include redefiningof the local traffic on railway lines class I!, then the employees,reorganisation and all the other transformations whichwill be carried out in continuity.